Recycling of crushed waste clay brick as aggregates in cement mortars: An approach from macro- and micro-scale investigation - Huang, Qian; Zhu, Xiaohong; Xiong, Guangqi; Wang, Chaoqiang; Liu, Dongsheng; Zhao, Liang (Construction & building materials, 2021)
The waste clay brick (WCB) was crushed and used as the fine aggregates to produce recycled mortars with sufficient workability (i.e. high water-cement ratio of 0.6). Two curing conditions (air and standard) and two statuses of WCB (dry and pre-soaking) were considered in this study. It was found that the recycled mortars with the dry WCB had relatively higher mechanical properties and lower water absorption but a converse tendency for pre-soaking WCB mortars, regardless of the curing conditions. Although the internal curing effect of WCB was more pronounced under the air condition, the overall performance of recycled mortars cured in the standard condition was better. Microstructural changes were then investigated through X-ray diffraction (XRD), thermogravimetric-differential scanning calorimetry (TG-DSC), scanning electron microscopy (SEM), and mercury intrusion porosimetry (MIP) to support the macro property changes of recycled mortars. As evaluated by TG-DSC, the hydration degree of cement in the recycled mortar with dry WCB were greater than that of reference group without WCB, and the hydration degree further increased when the natural aggregates were replaced by the pre-soaking WCB. Regardless of the curing conditions, the WCB aggregate were tightly bonded by cement paste in the recycled mortar with dry WCB, and the interfacial transition zone (ITZ) between them was more compact. Conversely, the interval between pre-soaking WCB and cement matrix was observed. The incorporation of dry or pre-soaking WCB increased the porosity of recycled mortars. The recycled WCB mortars could be used for producing the cleaner building materials.